Deep Learning for Classification of Peak Emotions within Virtual Reality Systems - Quesnel, Denise; DiPaola, Steve; Riecke, Bernhard E. (International SERIES on Information Systems and Management in Creative eMedia (CreMedia), 2018)
Research has demonstrated well-being benefits from positive, ‘peak’ emotions such as awe and wonder, prompting the HCI community to utilize affective computing and AI modelling for elicitation and measurement of those target emotional states. The immersive nature of virtual reality (VR) content and systems can lead to feelings of awe and wonder, especially with a responsive, personalized environment based on biosignals. However, an accurate model is required to differentiate between emotional states that have similar biosignal input, such as awe and fear. Deep learning may provide a solution since the subtleties of these emotional states and affect may be recognized, with biosignal data viewed in a time series so that researchers and designers can understand which features of the system may have influenced target emotions. The proposed deep learning fusion system in this paper will use data collected from a corpus, created through collection of physiological biosignals and ranked qualitative data, and will classify these multimodal signals into target outputs of affect. This model will be real-time for the evaluation of VR system features which influence awe/wonder, using a bio-responsive environment. Since biosignal data will be collected through wireless, wearable sensor technology, and modelled through the same computer powering the VR system, it can be used in field research and studios.
Keywords: AI; IAT813; IAT813_Spring2017; NSERC DG 2026; Riecke; Riecke_2018; bernhard-riecke; deep learning; denise-quesnel; earthgazing; journalPaper; steve-dipaola